2020
DOI: 10.3389/fpsyg.2020.00758
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior Predicts Quality, Creativity, and Efficiency Performance: The Roles of Occupational and Collective Efficacies

Abstract: Although numerous studies have shown that prosocial behavior impacts performance within organizations, the mechanisms that encourage or discourage these effects have rarely been explored. Two studies were conducted to shed light on the role of psychological beliefs on prosocial dynamics in predicting organizational performance. In Study 1, employees' beliefs in their inner job-related resources (Occupational Efficacy-OE) were examined as a predictor of OCB. It was posited that OE, which is an inner resource, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 66 publications
2
40
0
2
Order By: Relevance
“…Generally, OCB has been found to be related to teacher efficacy and workplace spirituality (Choong, Ng, Ai Na, & Tan, 2019;Mahipalan & Muhammed, 2019) and reduced turnover intention (Risa & Purba, 2019). It has also been reported that OCB predicts quality, creativity and efficient performance (Yaakobi & Weisberg, 2020). Organisational citizenship behaviour is a function of Orientation: The exhibition of organisation citizenship behaviour (OCB) by teachers is of great benefit for human capital development.…”
mentioning
confidence: 99%
“…Generally, OCB has been found to be related to teacher efficacy and workplace spirituality (Choong, Ng, Ai Na, & Tan, 2019;Mahipalan & Muhammed, 2019) and reduced turnover intention (Risa & Purba, 2019). It has also been reported that OCB predicts quality, creativity and efficient performance (Yaakobi & Weisberg, 2020). Organisational citizenship behaviour is a function of Orientation: The exhibition of organisation citizenship behaviour (OCB) by teachers is of great benefit for human capital development.…”
mentioning
confidence: 99%
“…With very high level of OCBs, the findings imply that the respondents may also have high level of self-efficacy, sense of self-fulfilment, and teaching efficacy and performance (Mallick, et al, 2014;Organ, 2018;Somech, & Oplatka, 2015;Wei, 2014). Findings also indicate that respondents may yield more teaching quality and innovation (Yaakobi &Weisberg, 2020), knowledge sharing, job satisfaction, mental health, physical health, job retention, and learner-centered behaviors (De Geus, et al, 2020;Hazzi, 2018). The respondents' level of OCBs further implies that the organization (school) where they work at may have organizational efficiency and effectiveness (De Geus, et al, 2020;Hazzi, 2018;Organ, 2018) and higher productivity and better quality of service (Somech & Oplatka, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…OCB is found to be helpful in promoting quality and innovation in organization (Yaakobi &Weisberg, 2020). It facilitates knowledge sharing and promotes job satisfaction, mental health, physical health, job retention, and service-oriented behaviors among employees (De Geus, Ingrams, Tummers, & Pandey, 2020).…”
Section: Literature Review Organizational Citizenship Behaviormentioning
confidence: 99%
“…Studies have been conducted to determine the effect of organizational citizenship and the performance of an organization. Yaakobi and Weisberg (2020) studied the effect of organizational citizenship behaviour toward quality, creativity, and efficiency performance.…”
Section: The Importance Of Supportive Work Environment For Ocbmentioning
confidence: 99%